Combined purebred and crossbred genetic evaluation of Columbia, Suffolk, and crossbred lamb birth and weaning weights: systematic effects and heterogenous variances - Vargas Jurado, Napoleón; Notter, David R; Taylor, Joshua B; Brown, Daniel J; Mousel, Michelle R; Lewis, Ronald M (Oxford University Press (OUP), 2024)
Despite the benefits of crossbreeding on animal performance, genetic evaluation of sheep in the U.S. does not directly incorporate records from crossbred lambs. Crossbred animals may be raised in different environments as compared to purebreds. Systemic factors such as age of dam and birth and rearing type may, therefore, affect purebred and crossbred performance differently. Furthermore, crossbred performance may benefit from heterozygosity, and genetic and environmental variances may be heterogeneous in different breeds and their crosses. Such issues must be accounted for in a combined (purebred and crossbred) genetic evaluation. The objectives of this study were to i) determine the effect of dam age and birth type on birth weight, and dam age and birth-rearing type on weaning weight, in purebred and crossbred lambs, ii) test for heterogeneous genetic and environmental variances in those weights, and iii) assess the impact of including weights on crossbred progeny on sire estimated breeding values (EBV). Performance records were available on purebred Columbia and Suffolk lambs. Crossbred information was available on lambs sired by Suffolk, Columbia or Texel rams mated to Columbia, Suffolk, or crossbred ewes. A multiple-trait animal model was fitted in which weights from Columbia, Suffolk, or crossbred lambs were considered different traits. At birth, there were 4,160, 2,356, and 5,273 Columbia, Suffolk, and crossbred records, respectively, with means (SD) of 5.14 (1.04), 5.32 (1.14), and 5.43 (1.23) kg, respectively. At weaning, on average at 122 (12) d, there were 2,557, 980, and 3,876 Columbia, Suffolk, and crossbred records, respectively, with corresponding means of 39.8 (7.2), 40.3 (7.9), and 39.6 (8.0) kg. Dam age had a large positive effect on birth and weaning weight in pure and crossbred lambs. At birth, however, the predicted effect was larger in crossbred and Suffolk lambs. While an increase in a number of lambs born and reared had a strong and negative influence on birth and weaning weight, the size of the effect did not differ across-breed types. Environmental variances were similar at birth and weaning, but additive variances differed among breed types for both weights. Combining purebred and crossbred information in the evaluation not only improved predictions of genetic merit in purebred sires but also allowed for direct comparisons of sires of different breeds. Breeders thus can benefit from an additional tool for making selection decisions.
Keywords: crossbreeding; multiple-trait evaluation; systematic effects; validation